Determinants of e-wallets continued usage intention - Fragata, Anabela; Pinto, Diana; Cruz- Lopes , Luisa; Oliveira, Carla (Millenium - Journal of Education, Technologies, and Health, 2025)
Introduction: E-wallets streamline transactions for consumers by consolidating credit cards, cash, and various payment platforms into one convenient device; thus, these contactless payment transactions have seen a notable surge in Portugal in recent years. Objective: The purpose of this paper is to empirically examine the determinants that influence a consumer´s continued usage intention to use E-wallets in Portugal. Methods: Data were analyzed by employing exploratory and confirmatory analysis, and a Structural Equation Model was extracted from 185 Portuguese respondents. Results: Data revealed that performance expectancy, effort expectancy, facilitating conditions, and perceived trust are important determinants of behavioral intention and will positively impact continued intention to use E-Wallets. Perceived reputation and perceived security are also determinants of perceived trust. Conclusion: Therefore, continuous improvement in these areas is imperative to enhance the e-wallet’s performance and competitiveness over alternative transactions.